### Home > CAAC > Chapter 4 > Lesson 4.1.2 > Problem 4-13

4-13.

Write the equation represented in the equation mat below. Homework Help ✎

Simplify as much as possible and then solve for

*x*.Check your solution.

Flip subtraction to addition.

Remove zero pairs.

Combine like terms.

Add 4 to both sides.

Subtract *x* from both sides.

Divide by 2 on both sides.

Right now the equation is:

*x* + 1 + −2 −(−2*x*+3) = *x* + 5 −(2 + −1)

*x* +1 + (−2) + 2*x* + (−3) = *x* +5 + −2 + 1

3*x* + (−4) = *x* + 4

3*x* = *x* + 8

2*x* = 8

*x* = 4

Substitute your answer from part (a) into the original equation.